1991
DOI: 10.2307/2295485
|View full text |Cite
|
Sign up to set email alerts
|

Television's Role in the Socialization of African American Children and Adolescents

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Television's role in the socialization of African-American children and adolescents and its potential to influence their development was the focus of Stroman's (1991) study. The author views television as a mode of vicarious socialization which competes with the other socializing agents present in the lives of children.…”
Section: Media Portrayal Of African-americansmentioning
confidence: 99%
“…Television's role in the socialization of African-American children and adolescents and its potential to influence their development was the focus of Stroman's (1991) study. The author views television as a mode of vicarious socialization which competes with the other socializing agents present in the lives of children.…”
Section: Media Portrayal Of African-americansmentioning
confidence: 99%
“…1,2 Given that Latino preschool children are at greater risk for obesity than other children, 3 understanding television viewing in this population is warranted. While there is considerable literature regarding the television viewing habits of white and African American children, [4][5][6][7] there is limited research on television viewing in Latino children. Furthermore, none of this work takes into account the ethnic subgroups of Latinos.…”
mentioning
confidence: 99%
“…First, African American children and adolescents regard television as an important source of information (Stroman, 1991) and tend to watch more of it (Brown & Pardun, 2004;Kaiser Family Foundation, 2005;Roberts, 2000;Roberts & Foehr, 2008;Stroman, 1991;Wartella, Alexander, & Lemish, 1979), become more involved in programs (Greenberg & Atkin, 1982), perceive it as more real (Poindexter & Stroman, 1981), and use it more for socialization purposes (Poindexter & Stroman, 1981) than do Caucasian children. Jackson, Brown, and Pardun (2008) found that African American adolescents were more likely than Caucasian adolescents to have three or more televisions in their household, including having a television in their own bedroom.…”
Section: Generalizing Mediation Research To Other Populationsmentioning
confidence: 99%
“…African American children watch more television than do Caucasian children (Brown & Pardun, 2004;Kaiser Family Foundation, 2005;Stroman, 1991;Wartella et al, 1979) and may be more likely to experience some negative effects from viewing. In this sense, the research on mediation has yet to address one of television's most vulnerable audiences.…”
Section: Mediation and Nontraditional Gender Rolesmentioning
confidence: 99%